Belwederczycy i podchorazowie - Bielecki, Robert (Warszawa : Krajowa Agencja Wydawnicza, 1989)
A history of the aborted November uprising of 1830, carried out by the military cadets against the Russian occupiers of Poland.
Keywords: Poland -- History -- Revolution, 1830-1832.